Economic Empowerment of Persons with Disabilities through the Development of Tempe Chips MSMEs: Pemberdayaan Ekonomi Penyandang Disabilitas melalui Pengembangan UMKM Keripik Tempe - Tanjung, Ahmad Albar; Chaniago, Eva Nirmala Sari; La Ane, La Ane; Triadiarti, Yulita (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in strengthening the national economy because they contribute significantly to job creation and improving community welfare. Deli Serdang Regency is one of the regions with great potential for developing tempeh-based agro-industry, particularly tempeh chips, which are part of the local food value chain. However, the Asyifa MSME, managed by people with disabilities, faces serious obstacles in the initial stages of production, namely the manual, unhygienic process of peeling soybean skins, which takes 2–3 days to complete one production cycle. This condition reduces work efficiency, product quality, and business competitiveness in the local market. This community service program aims to address these problems through the application of appropriate technology in the form of a soybean skin peeling machine (dehuller) designed according to partner needs. Activities are implemented through structured stages that include participatory planning with partners,Focus Group Discussion (FGD) to identify technical and operational needs, technical training on machine use and maintenance, official handover of equipment, and intensive mentoring during the implementation phase to ensure the technology can be operated optimally and sustainably. The evaluation results showed a significant improvement in production performance. The soybean peeling process, which previously required 2–3 days, can now be completed in less than one day for each production cycle. The level of product cleanliness and uniformity has also increased to 90%, while production capacity has increased by approximately 40% compared to conditions before the technology implementation. Overall, the implementation of this appropriate technology has proven effective in increasing production process efficiency, maintaining the quality of processed products, and strengthening the competitiveness of MSMEs in an inclusive manner